2020
DOI: 10.1186/s12889-020-09552-1
|View full text |Cite
|
Sign up to set email alerts
|

“A loving man has a very huge responsibility”: A mixed methods study of Malawian men’s knowledge and beliefs about cervical cancer

Abstract: Background In Malawi, numerous barriers may prevent women from accessing cervical cancer screening services — including social factors such as male partner involvement. We conducted surveys that included open- and closed-ended questions with married Malawian men to evaluate their knowledge and beliefs about cervical cancer. Methods HIV-positive adult (≥18 years) men (married or in a stable relationship) were recruited from an antiret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
(73 reference statements)
0
5
0
Order By: Relevance
“… 18 If male partners have concerns about health procedures, they are often unwilling to provide moral support and financial assistance. 19 For example, one participant described her partner’s negative reaction to condoms. Stigma surrounding condoms is often associated with prostitution.…”
Section: Resultsmentioning
confidence: 99%
“… 18 If male partners have concerns about health procedures, they are often unwilling to provide moral support and financial assistance. 19 For example, one participant described her partner’s negative reaction to condoms. Stigma surrounding condoms is often associated with prostitution.…”
Section: Resultsmentioning
confidence: 99%
“…This finding aligns with a study done in Malawi which demonstrated that men under 45 were more likely to have a positive attitude towards gender equity in sexual matters and were more actively involved in their partner's screening. 12 The area of residence of the participants was also associated with male involvement in cervical cancer screening. The physical environment and the social determinants of health shape healthcare behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research has indicated that male partners have a desire to actively participate in decision-making about cervical cancer screening. Nevertheless, the individuals possessed a restricted understanding regarding the process of screening and maintained inflexible attitudes towards societal expectations of gender, which subsequently influenced their endorsement of cervical cancer screening (Chapola et al, 2021;Kim, Kim & Kim, 2018;Lewis et al, 2020;Rosser et al, 2014). Previous studies have indicated that the presence of negative attitudes among women, along with their perceived susceptibility to developing cervical cancer and perceived hurdles, can diminish the probability of engaging in cervical cancer screening (Bayu et al, 2016;Idowu et al, 2016;Nigussie et al, 2019).…”
Section: Yes 84%mentioning
confidence: 99%